Ranking da Transparência do Ministério Público Federal: Análise entre os Municípios mais Transparentes de São Paulo - Silva, Erico Gustavo Tomaz Da [UNIFESP] (2019)
This study aims to develop a comparative analysis among the most transparent municipalities of the State of São Paulo, based on a research, which originate the Brazilian ranking of transparency published by the Federal Public Ministry. Based on the work team composed by several control and inspection agencies, called the National Strategy to Combat Corruption and Money Laundering, a form was created based on Law 12,527 / 2011 (Law on Access to Information) , Law No. 101/2000 (Fiscal Responsibility Law), Decree No. 7,195 / 2010 (which provides for the minimum quality standard of the integrated financial administration and control system, within each Federation body), and with some items that are considered good transparency practices. The research highlighted several devices for active and passive transparency and the strong presence of indicators describing access to information and transparency consistent with legal and normative instruments. The methodology adopted in this work is the study of multiple cases, which aims to understand in depth the ways and strategies pursued by these municipalities to achieve such satisfactory levels of public transparency. The results indicated that the coercive power of the MPF, through public civil actions, extrajudicial and judicial actions, was a determining factor, in a short time, 120 days, so that the index of transparency in the Brazilian municipalities and states could be improved. The survey also found that the most transparent municipalities are not among the eight richest in the state of São Paulo, as evidenced in this sample, that the economic factor and the complexity of the administrative structure may not be a determining factor for Public Management to become more transparent. Furthermore, this study contributes to highlight the procedures and strategies that may be useful to municipalities that have not yet reached what was expected in the construction and improvement of their transparency portal.